Valoración Bromatologíca de cinco especies forrajeras nativas de la Amazonía Sur del Ecuador en seis estadios fenológicos - Viñamagua Guaya, Mariana de Jesus (2018)
He present work was developed in the El Padmi Experimental Farm located 5 km from the Los Encuentros parish, in the Yantzaza canton, it started on May 25, 2017 and ended on November 24, 2017. Five native forage species were evaluated. the southern Amazon of the equator in six phenological stages: Tithonia diversifolia or Golden Button, Lasiacis sorghoidea or forage chin, Munnozia hastifolia or Lechosa, Clibadium sp or Padmi 1 and Urera caracasana or Chine forager; vegetative, elongation, floral bud, initial flowering, full flowering and seed dissemination. A factorial arrangement of 5 x 6 (tree species by phenological stages) was used with 30 treatments and six repetitions; the variables analyzed were plant height, main stem diameter, number of branches, biomass production and chemical composition. The results show that shrubs with the best nutritional value and optimal phenological stage for cutting are in full flowering and seed dissemination in the Golden Button species with 17.72% protein, dry matter 19.21%, ashes 16.30% ethereal extract, with 3.72% crude fiber 25.32% and extracted nitrogen-free 37.25% and fodder chine in the initial flowering stage with 21.79% crude protein, 17.32% dry matter; 19.40% ash, ethereal extract 1.18%; crude fiber 29.91 and nitrogen-free extract 27.72%. Button of Gold reaches heights of 182.33 cm and 279.58; diameter 13.30 and 13.79 mm with average of 14.31 branches with a biomass of 4.3 kg / plant and Chine fodder 124.8 cm height, diameter 13.36 mm, 4.80 branches and 2, 72 kg / biomass plant. Taking into account the best result that in this case is Button of gold and Chine fodder, a proposal was made to cultivate them in forage banks. Key words: bush fodder, phenological stages, nutritional value.